A symbiotic view of the origin of life at hydrothermal impact crater-lakes. Issue 30 (29th April 2016) - Chatterjee, Sankar
Abstract : Submarine hydrothermal vents are generally considered as the likely habitats for the origin and evolution of early life on Earth. Abstract : Submarine hydrothermal vents are generally considered as the likely habitats for the origin and evolution of early life on Earth. The theory suffers from the 'concentration problem' of cosmic and terrestrial biomolecules because of the vastness of the Eoarchean global ocean. An attractive alternative site would be highly sequestered, small, hydrothermal crater-lakes that might have cradled life on early Earth. A new symbiotic model for the origin of life at hydrothermal crater-lakes is proposed here. Meteoritic impacts on the Eoarchean crust at the tail end of the Heavy Bombardment period might have played important roles in the origin of life. Impacts and collisions that created hydrothermal crater lakes on the Eoarchean crust inadvertently became the perfect crucibles for prebiotic chemistry with building blocks of life, which ultimately led to the first organisms by prebiotic synthesis. In this scenario, life arose through four hierarchical stages of increasing molecular complexity in multiple niches of crater basins. In the cosmic stage (≥4.6 Ga), the building blocks of life had their beginnings in the interstellar space during the explosion of a nearby star. Both comets and carbonaceous chondrites delivered building blocks of life and ice to early Earth, which were accumulated in hydrothermal impact crater-lakes. In the geologic stage (∼4 Ga), crater basins contained an assortment of cosmic and terrestrial organic compounds, powered by hydrothermal, solar, tidal, and chemical energies, which drove the prebiotic synthesis. At the water surface, self-assembled primitive lipid membranes floated as a thick oil slick. Archean Greenstone belts in Greenland, Australia, and South Africa possibly represent the relics of these Archean craters, where the oldest fossils of thermophilic life (∼3.5 Ga) have been detected. In the chemical stage, monomers such as nucleotides and amino acids were selected from random assemblies of the prebiotic soup; they were polymerized at pores of mineral surfaces with the coevolution of RNA and protein molecules to form the 'RNA/protein world'. Lipid membranes randomly encapsulated these RNA and protein molecules to initiate a molecular symbiosis in a 'RNA/protein/lipid world' that led to hierarchical emergence of several cell components: plasma membranes, ribosomes, coding RNA and proteins, DNA, and finally protocells with a primitive genetic code. In the biological stage, the emergence of the first cells capable of reproduction, heredity, variation, and Darwinian evolution is the key breakthrough in the origin of life. RNA virus and prions may represent the evolutionary relics of the RNA/protein world that survived as parasites for billions of years. Although the proposed endosymbiotic model is speculative it has intrinsic heuristic value. Future experiments on encapsulated RNA virus and prions have the potential to create a synthetic cell that may confirm a coherent narrative of this hierarchical evolutionary sequence.